KINERJA PELAYANAN PADA KANTOR BADAN PERTANAHAN NASIONAL KABUPATEN GORONTALO - Norma L.P. Wemben (JURNAL LEGALITAS, 2010)
one of the main factors in creating crean governance (crean government) and good governance (good governance) is to improve the peformance of government services. Principles such as productivity, customer satisfaction, responsiveness, responsibility, and occountability, are considered imporiant in the creation of bureaucratic climate that \'heolthy\'. in the context of public service,performonce improvement officers will determine the eficiency and quality of service to the community. The results showed that the performance aspect of the service of responsiveness, responsibility, productivity, and accountability and customer satisfaction in Gorontalo BPN office is good enough. as tha authors previously found that a good service peformance is influenced by a factor of one executive officer of service acivities, hich in this case the apparatus seen from the dimensions of commitment in providing service to the community. Recommendatians of this research is need for improvements in service quality from the office of BPN Gorontalo regency, this is based on increasing public awareness of the importance of having a certificate of ownership of land.Improving the quality of the service such as an increased commitment to appropriate authorities in completing the work at the appointed time. Keyword:Responsibilitas,produktifitas,Akuntabilitas, Custommer service.